The Assessment of Motor Performance Using Two Coordination Tests on Students with Cerebral Palsy- A Preliminary Study - Abdullah, Nagoor Meera; Akhir, Nor Hafiza Mohd; Tumijan, Wahidah; Hamid, Norlizah Abdul; Parnabas, Vincent; Nazarudin, Mohamad Nizam; Fauzee, Mohd Soffian Omar (Media Ilmu Keolahragaan Indonesia, 2014)
A regular physical activity has benefits on motor performance among student with cerebral palsy. In this study were investigating the assessment of motorperformance on eye-hand coordination and lower-body coordination between cerebral palsy. A total of 21 male and female students (n = 21) were involved from Penang Spastic Center. The anthropometrics were measured height and weight and two motor performance test were conducted namely target Throwing with Ball in Basket and AAHPERD ball-changing Zigzag Run Test. All the data were analyzed using SPSS and presented as mean of (± SEM). The mean age of all subjects were 18.00 ± 3.61 years old ranging from 12 – 24 years old. The majority of the subjects were Chinese 53%, followed by Malays 33.3% and 14% Indian. The mean value height and weight of all subjects were 150.1± 32.4 m and 59.9 ± 15.51 kg. The mean value for Target Throwing with Ball in Basket 0.90 ± 0.436 and AAHPERD Ball-changing Zigzag Run Test 0:01:22.19 ± 0:00:24.836 minutes. The test shows they are not much difference in upper and lower body coordination. However, on this studies are found people with cerebral palsy were low level on motor performance. Thus, more study on the designing and implementation of physical on motor performance program for people with cerebral palsy should be conducted in order to increase their physical performance level.